The management of open tibial fractures in children: a retrospective case series of eight years' experience of 61 cases at a paediatric specialist centre. (April 2017) - Nandra, R. S.; Wu, F.; Gaffey, A.; Bache, C. E.
Abstract : Aims: Following the introduction of national standards in 2009, most major paediatric trauma is now triaged to specialist units offering combined orthopaedic and plastic surgical expertise. We investigated the management of open tibia fractures at a paediatric trauma centre, primarily reporting the risk of infection and rate of union. Patients and Methods: A retrospective review was performed on 61 children who between 2007 and 2015 presented with an open tibia fracture. Their mean age was nine years (2 to 16) and the median follow-up was ten months (interquartile range 5 to 18). Management involved IV antibiotics, early debridement and combined treatment of the skeletal and soft-tissue injuries in line with standards proposed by the British Orthopaedic Association. Results: There were 36 diaphyseal fractures and 25 distal tibial fractures. Of the distal fractures, eight involved the physis. Motor vehicle collisions accounted for two thirds of the injuries and 38 patients (62%) arrived outside of normal working hours. The initial method of stabilisation comprised: casting in nine cases (15%); elastic nailing in 19 (31%); Kirschner (K)-wiring in 13 (21%); intramedullary nailing in one (2%); open reduction and plate fixation in four (7%); and external fixation in 15 (25%). Wound management comprised: primary wound closure in 24 (39%), delayed primary closure in 11 (18%), split skin graft (SSG) in eight (13%), local flap with SSG in 17 (28%) and a free flap in one. A total of 43 fractures (70%) were Gustilo-Anderson grade III. There were four superficial (6.6%) and three (4.9%) deep infections. Two deep infections occurred following open reduction and plate fixation and the third after K-wire fixation of a distal fracture. No patient who underwent primary wound closure developed an infection. All the fractures united, although nine patients required revision of a mono-lateral to circular frame for delayed union (two) or for altered alignment or length (seven). The mean time to union was two weeks longer in diaphyseal fractures than in distal fractures (13 weeks versus 10.8 weeks, p = 0.016). Children aged > 12 years had a significantly longer time to union than those aged < 12 years (16.3 weeks versus 11.4 weeks, p = 0.045). The length of stay in hospital for patients with a Gustilo-Anderson grade IIIB fracture was twice as long as for less severe injuries. Conclusion: Fractures in children heal better than those in adults. Based on our experience of deep infection we discourage the use of internal fixation with a plate for open tibial fractures in children. We advocate aggressive initial wound debridement in theatre with early definitive combined orthopaedic and plastic surgery in order to obtain skeletal stabilisation and soft-tissue cover. Cite this article: Bone Joint J 2017;99-B:544–53.